Cover Picture: Protein Surface Mimetics: Understanding How Ruthenium Tris(Bipyridines) Interact with Proteins (ChemBioChem 2/2017). (28th December 2016) - Hewitt, Sarah H.; Filby, Maria H.; Hayes, Ed; Kuhn, Lars T.; Kalverda, Arnout P.; Webb, Michael E.; Wilson, Andrew J.
Abstract : The cover picture shows competitive inhibition of the cytochrome c /cytochrome c peroxidase interaction by highly functionalized ruthenium(II) tris(bipyridine) complexes. Inhibition is achieved through recognition of the solvent‐exposed surface of cytochrome c using ruthenium(II) tris(bipyridine) complexes at the cytochrome c peroxidase binding site, as shown by 950 MHz natural‐abundance NMR spectroscopy and detailed fluorescence studies. Binding is driven by entropy and electrostatic effects with additional potency arising in higher‐affinity complexes from enthalpic contributions. More information can be found in the full paper by A. J. Wilson et al.page 223 in Issue 2, 2017 (DOI:10.1002/cbic.201600552 ).